Presence and Distribution of Human-Related Microsporidian Spores across Different Topsoil Areas across Alcalá de Henares (Spain) - Antonio Peña-Fernández; Manuel Higueras; María del Carmen Lobo-Bedmar; Fernando Izquierdo; Umar Anjum (Biology and Life Sciences Forum)
Humans can potentially be exposed to Enterocytozoon bieneusi and Encephalitozoon spp. from topsoils when playing or spending time in recreational areas. Two hundred and seventy-seven topsoil samples were collected across Alcalá de Henares (Spain) in July 2017: one hundred and fifty-five urban, sixty industrial and twelve from a public garden. Simultaneous detection was performed using a SYBR Green real-time PCR following the appropriate extraction of DNA with Fast-Prep for Soil®. The organic matter content (OM), pH, electrical conductivity (EC) and soil texture (percentages of sand, clay and silt) were also determined. E. bieneusi was detected in nine (five urban, four industrial); meanwhile, Encephalitozoon spp. was detected in 22 topsoil samples (sixteen urban, six industrial; ten E. intestinalis, nine E. intestinalis/E. hellem and three E. cuniculi). The presence of E. bieneusi was associated with urban soils that presented lower EC (0.50 vs. 0.71 dS/m; p-value = 0.0110), as this factor may provide a richer environment for the survival of spores. The presence of microsporidian spores was higher in those topsoils with a higher OM content for E. bieneusi (6.96% vs. 4.98%; p-value = 0.0342) and E. intestinalis/E. hellem in one of the four quadrants into which the urban area was divided (5.54% vs. 3.12%; p-value = 0.0007). E. intestinalis is present in industrial topsoils with significantly lower contents of sand (14.5% vs. 21.74; p-value = 0.00003) but higher contents of silt (78.5% vs. 64.9%; p-value = 0.0229), which might be attributed to the differences in the capacity of topsoils to retain moisture, depending on their texture. Moreover, the provision of enough oxygen might play a role in the higher presence of E. intestinalis/E. hellem in urban topsoils with lower contents of clay (11% vs. 19%; p-value = 0.0200). A better understanding of these potential associations is critical in selecting appropriate decontamination techniques and strategies to prevent and minimise human exposure.